Pengaruh Penyaluran Pembiayaan Mudharabah Dan Pembiayaan Musyarakah Terhadap Profitabilitas Bank Umum Syariah Indonesia Periode 2017-2021 - Wiwik Nuraini; Elen Puspitasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purposeiiof thisiistudy isiito examineiithe effectiiof the distribution financingiifrom Mudharabahiiand Musyarakahiion the profitabilityiiof Indonesian Sharia Commercial Banks. Thisiiresearch is aiiquantitative research. The population usediiis SyariahiiCommercial Banks which ithat haveiibeen registerediiin theiiOtoritas Jasa Keuangan for theiiperiod 2017-2021.iiThis study uses secondary data sourced from the financial statements of the Islamic Public Bank companies which have been published through the official website in the Otoritas Jasa Keuangan (OJK) at www.ojk.go.id .Purposive samplingiiis the methodiiused iniithis study to obtainii48 samples ofiidata from 14 Indonesian ShariaiiCommercial Banks.iiIn the study, the data analysis techniqueiiused is the classical assumption test and hypothesisiitesting using isiiimultiple lineariiregression with a significance level of 5% and assisted by the SPSSiiversion 19 program. The studyiishown the resultsiithat MudharabahiiFinancingiihas a positiveiieffect andiisignificantiion profitability of Sharia Commersial Banks.iiWhile the MusyarakahiiFinancing has no and negative effect and significant on the profitability of Sharia Commersial Banks. Keywords:Financing, Profitability,iMudharabah, Musyarakah,iReturn on Assets.